Climate change and urban forests: generational differences in women’s perceptions and willingness to participate in conservation efforts - Maleknia, Rahim; Elena Enescu, Raluca; Salehi, Tayebeh (Frontiers in Forests and Global Change, 2025)
IntroductionClimate change represents one of the most pressing challenges confronting contemporary societies. Despite occupying a relatively small proportion of the Earth’s surface, cities contribute disproportionately to greenhouse gas emissions. Urban forests, as a vital form of natural infrastructure, play a critical role in mitigating the adverse impacts of climate change. Effective management and conservation of these resources necessitate active engagement from diverse stakeholder groups, with women being a particularly important demographic. However, generational differences in women’s perceptions of climate change and their willingness to participate in urban forest conservation have received limited investigation. This study seeks to address this gap by comparing the perceptions and conservation participation intentions of two groups of women: those belonging to Generation Z and women from earlier generations.MethodsThe sample comprised 401 women from Generation Z and 395 women from other generations. Data for the study were collected using a questionnaire administered through a multi-stage cluster sampling method. The collected data encompassed participants’ awareness of climate change, its causes, the dual impacts of climate change and urban forests, their willingness to engage in urban forest management, and their demographic characteristics such as age, educational level, family size, family income, highest education in family, and educational levels of fathers and mothers. The analysis was conducted using both descriptive and inferential statistical methods.ResultsThe results revealed significant generational differences in understanding climate change, recognizing the role of forests in mitigating its effects, and demonstrating willingness to engage in urban forest conservation. Across all measures, Generation Z exhibited higher levels of awareness and willingness compared to older generations. Furthermore, increased awareness of these issues in both groups was positively associated with a greater willingness to participate in urban forest management. Socio-economic factors also influenced willingness differently between the two generational groups, highlighting the nuanced effects of these variables on participation intentions.DiscussionThe results showed althought differences in awareness were observed between the two groups, increased awareness consistently led to a heightened willingness among both groups to participate in urban forest conservation. These findings underscore the importance of adopting intergenerational perspectives on climate change, emphasizing that educational and promotional programs must be tailored to account for generational differences to effectively maximize engagement and foster widespread participation in urban forest conservation efforts.